The Effect of Environmental Factors on Microbial Growth - Rhezqy Furwati Jufri (Journal La Lifesci, 2020)
Chemical factors that have inhibition based on the results of this practicum are Tetracycline and formalin. In this experiment, no type of liquid bath soap was found that inhibited the growth of E. coli. This can occur because of an error in the experimental procedure. Escherichia coli bacteria can grow optimally in the temperature range of 30 ° C. Formalin has a strong inhibitory effect on the growth of Escherichia coli bacteria, as well as Tetracycline antibiotics which can inhibit the growth of E. coli bacteria.